THE SIGNIFICANCE OF MINDFULNESS MODULE TO REDUCE AGGRESSION AMONG PRISON INMATES - Chethiyar, Saralah Devi Mariamdaran; Rukumangadan, Rathiga K (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of this research was to examine the positive effect of mindfulness among female prison inmates who are aggressive. Quantitative Quasi-experimental research methodology was used in this research where the empirical intervention was studied using purposive sampling. The sample consisted of 36 female inmates from one of the prisons in the Malaysian state. They were tested for mindfulness techniques and the measures were taken before and after intervention for six weeks. The research was conducted using survey questionnaires. Measurements were made using the “Mindful Attention Awareness Scale” for the measurement of mindfulness. Aggression questionnaire developed by Buss & Perry was used to measure aggression of inmates in terms of Physical Aggression (PA), Verbal Aggression (VA), Anger (A), and H (Hostility). The data collected were analyzed with SPSS version 25. The findings indicated that there is a correlation between mindfulness and aggression. The study also indicated that those who had practiced mindfulness showed less aggression, and built a strong bond with other participants in the group. There were limitations to the prison environment due to security reasons. Thus, it is recommended that the study be conducted in a non-prison environment to further strengthen the findings.